New records of the water mite genus Arrenurus from Iran, with the description of two new species from Iran and Cyprus (Acari, Hydrachnidia, Arrenuridae). Zootaxa, 1152, 59–68. (ERRATUM) - Smit, H.; Pesic, V. (Zootaxa, 2006)
(ERRATUM)